Pre-Service Perspectives on E-Teaching: Assessing E-Teaching Using the EPEC Hierarchy of Conditions for E-Learning/Teaching Competence - Ashley Sisco; Stuart Woodcock; Michelle Eady (The Canadian Network for Innovation in Education (CNIE), 2015)
This article examines pre-service teacher perspectives of teaching with an online synchronous (live-time) platform as a part of their training. Fifty-three students who participated in a blended learning (including both face-to-face and online lectures) course were assessed in a teaching simulation through an online presentation, and participated in questionnaires and interviews about their experiences as e-learners using the platform. The EPEC hierarchy of conditions (Ease of use, Psychologically safe environment, e-learning/e-teaching Efficacy, and e-learning Competence) for e-learning competency, developed based on an analysis of pre-service teachers' experience as e-learners in this same study, was used as a framework to assess teacher perspectives as e-teachers using this technology. Qualitative interview data were collected about students' experiences using the platform, and analyzed via thematic content analysis. The findings showed that students generally favoured the online e-teaching synchronous platform over in-person presentations, and the quality of online presentations was considered at least as good as in person.